Parâmetros constitucionais da colaboração premiada - Melo, Caio Vanuti Marinho de (2021)
The present study analyzes the constitutional conformity of the award-winning collaboration with the guarantee of due process of law and the constitutional theory of criminal procedure. The research is justified insofar as it seeks to contribute to the evolution in the theoretical treatment of award-winning collaboration, besides to suggests modifications in the practice of the institute. The research has as method the deductive approach to the theme and will use of bibliographic research, critical analysis of legislation, jurisprudence, collaboration agreements and statistical data. At first, it is investigated the expansion movement of criminal justice of negotiation in the world, with focus on the efficiency bias of this movement and on the possibility of review of the fundaments of collaboration, in order to make it compatible with a process model of guarantees. In addition, it is studied how criminal justice of negotiation occurs in the United States of America, namely, the plea bargain system, specially its history, modalities and mainly the local critics to it. It starts with the dogmatic study of awardwinning collaboration, from the definition of its concept and legal nature, to, from there, define the assumptions and requirements of the agreement, its object, that is to say, the benefits, waivers and obligations of the collaborator, its procedure, which is divided in four phases: negotiation, formalization and homologation, effective collaboration and granting of benefits, and, at last, the anticipated forms of resolution of the agreement, that are the retraction and termination. At the last moment, the specific conflicts between the negotiating practice and some guarantees of due legal process are studied. First, they focus on the so-called organic guarantees of the criminal process (independence, impartiality and accusatory structure) in order to reveal the magistrate's role in a consensual criminal process. Subsequently, the focus switches to procedural guarantees, especially the guarantees of full defense and adversarial proceedings and their restriction in relation to the co-defendants accused, the non-waiver of the right to silence and its results, the necessity to overcome the regime of secrecy of collaboration, establishing a one of publicity after receiving the complaint, and the reflexes on the principle of presumption of innocence, especially in the biases of trial rule and probative rule. From this approach, award-winning collaboration is an institute that, in order to be considered constitutional, must adapt certain practices, such as the adoption of the judge of guarantees, the respect for the strict limits of the accusatory and judiciary functions, the permission to the co-defendants to contest the collaboration agreement and always manifest or speak after the collaborating defendant, the recognition of the non-waiver of the right to silence, the adoption of a collaboration regime of publicity and, finally, the impediment of the collaborator to insert illegal evidence through collaboration.